Analysis of the Risks of Small and Medium-Sized Enterprises in the Zilina Region - Maria Hudakova; Katarina Buganova; Jan Dvorsky; Jaroslav Belas; Leo-Paul Dana (Communications - Scientific letters of the University of Zilina, 2015)
Small and medium-sized enterprises (SMEs) are very sensitive to changes in the business environment which after a certain time are always reflected into quantitative characteristics of this sector. In 2013, we accomplished a statistical survey on current trends in the field of business risks for SMEs in selected regions of the Czech Republic and Slovakia. In this article we want to analyze the effects of selected risks of the survey with respect to the length of the small and medium-sized business enterprises in the Zilina region. SMEs should be aware of their risks, mainly due to their importance in the economic system of the Slovak Republic, which mostly lies in their inconsiderable share to create job positions in the region.